2020
DOI: 10.1177/0959651820953254
|View full text |Cite
|
Sign up to set email alerts
|

A rapid neural network–based state of health estimation scheme for screening of end of life electric vehicle batteries

Abstract: There is growing interest in recycling and re-use of electric vehicle batteries owing to their growing market share and use of high-value materials such as cobalt and nickel. To inform the subsequent applications at battery end of life, it is necessary to quantify their state of health. This study proposes an estimation scheme for the state of health of high-power lithium-ion batteries based on extraction of parameters from impedance data of 13 Nissan Leaf 2011 battery modules modelled by a modified Randles eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…A related example focusing on the end-of-life screening of batteries was proposed by [30] based on measurements of battery parameters by hybrid pulse power characterisation (HPPC), which was shown to be effective at estimating the state of health with low error with the use of a small dataset. In our previous work [31], a similar concept was explored using a small dataset based on EIS measurements with ECM-based parameter extraction; we demonstrated that this method presented large improvements in measurement times over conventional SoH measurement methods while retaining low estimation error. However, the previous work does not address the limitation of the lack of temperature dependence and relies on a well-chosen ECM for best results.…”
Section: Eis and Model-based State Of Health Estimationmentioning
confidence: 99%
See 2 more Smart Citations
“…A related example focusing on the end-of-life screening of batteries was proposed by [30] based on measurements of battery parameters by hybrid pulse power characterisation (HPPC), which was shown to be effective at estimating the state of health with low error with the use of a small dataset. In our previous work [31], a similar concept was explored using a small dataset based on EIS measurements with ECM-based parameter extraction; we demonstrated that this method presented large improvements in measurement times over conventional SoH measurement methods while retaining low estimation error. However, the previous work does not address the limitation of the lack of temperature dependence and relies on a well-chosen ECM for best results.…”
Section: Eis and Model-based State Of Health Estimationmentioning
confidence: 99%
“…A number of folds, typically K − 1, may then be reserved for training the network, while the remainder of the folds may be held-out as validation and testing data to evaluate the model. For this study, a value of K = 6 was chosen as a balance between validation accuracy and training performance as with our previous work [31]. For network evaluation and comparison, the metrics of RMS and mean absolute error, defined as…”
Section: Preprocessing and Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…SoH can be estimated by simple statistic methods, such as direct capacity test, but this type of methods will cost much time to obtain SoH as experimental result. As previously mentioned, ANNs considered an effective solution for handling with the behaviour of non-linear systems, cross-interaction between system variables and existing patterns in the data used to train the network [28] [29].…”
Section: B Soh-estimation Using Neural Networkmentioning
confidence: 99%
“…Among these methods, capacity-based methods, [9][10][11] impedance spectroscopy 7,[12][13][14][15] and Kalman filtering methods are commonly used to estimate the battery model parameters that can be considered as battery health indicators. [16][17][18][19][20] Capacity-based SoH methods can result in extremely accurate and reasonably straight forward measurements, 21 but this test is a very time-consuming process that requires the cell to be fully charged and discharged to carry out the current integration. 22,23 On the other hand, the internal resistance can be determined through both pulse power tests and the use of electrochemical impedance spectroscopy (EIS).…”
Section: Introductionmentioning
confidence: 99%